Evaluations of effects of sleep surfaces on athletic performance in youth - Maruyama, T.; Sato, S.; Matsumura, M.; Ono, T.; Nishida, M.; Nishino, S. (Scientific Reports, 2020)
We recently demonstrated that sleeping on high rebound [HR] mattress toppers induced a continuous and more rapid decline in core body temperature compared to low rebound [LR] mattress toppers during the initial phase of nocturnal sleep in young healthy volunteers. HR toppers are characterized by their supportive feel and high breathability whereas LR toppers are pressure-absorbing. In the current study, we evaluated effects of HR mattress toppers on objectively-(actigraphy) and subjectively-(questionnaires) evaluated sleep, vigilance (psychomotor vigilance test), and athletic performance (40-m sprint time, long jump distance, and star drill time) in youth male athletes age 10-19, in two sessions: fifty-one subjects in 2013 (study I) and 23 subjects in 2014 (study II). Sleeping on HR mattress toppers for four to six weeks improved some athletic performance measures compared to sleeping on LR or sleeping directly on spring mattresses without a topper. Statistically significant improvements in 40-m sprint time in study I (compared to LR) and in star drill time in study II (no topper) were observed. No changes in sleep and psychomotor vigilance were observed. These results suggest selecting optimal sleep surfaces may contribute to the maximization of athletic performances, and further studies are warranted.